Tinjauan Fikih Muamalah Atas Produk Jasa Berbasis Ujrah (Fee Based Services) Bank Konvensional (Sampel Produk Bank Mandiri dan BCA) - Muhammad Nurul Alim (Jurnal Asy-Syukriyyah, 2018)
Review of Fikih Muamalah on Products of Conventional Bank’s Fee-Based Services (Sample of Bank Mandiri and BCA Products). Although Islamic banks offer products of services which have the same kind and purpose as those are offered by conventional banks, most Moslems in Indonesia have not loyally make use all Islamic bank products for their financial transactions. Should the exercise of conventional bank’s services’ products be unavoidable, Moslems must be able to select and decide either the services are legal or illegal. This paper will study the fikih muamalah point of view on the conventional bank services that the customers will not fall in the usury transactions.